a: 2x+16=30
=>2x=30-16=14
=>x=14/2=7
b: \(2\left(x+1\right)^3+5=59\)
=>\(2\left(x+1\right)^3=54\)
=>\(\left(x+1\right)^3=27\)
=>x+1=3
=>x=2
c: \(x\inƯ\left(24\right)\)
=>\(x\in\left\{1;2;3;4;6;8;12;24\right\}\)
mà 2<=x<=12
nên \(x\in\left\{2;3;4;6;8;12\right\}\)
d: \(x-2⋮5\)
=>\(x-2\in\left\{0;5;10;15;20;25;30;35;...\right\}\)
=>\(x\in\left\{2;7;12;17;22;27;32;...\right\}\)
mà x<=30
nên \(x\in\left\{2;7;12;17;22;27\right\}\)
a) 2.x + 16 = 30
2x = 30 - 16
2x = 14
x = 14 : 2
x = 7
b) 2.(x + 1)³ + 5 = 59
2.(x + 1)³ = 59 - 5
2.(x + 1)³ = 54
(x + 1)³ = 54 : 2
(x + 1)³ = 27
(x + 1)³ = 3³
x + 1 = 3
x = 3 - 1
x = 2
c) x ∈ Ư(20) = {1; 2; 4; 5; 10; 20}
Mà 2 ≤ x ≤ 12
⇒ x ∈ {2; 4; 5; 10}
d) (x - 2) ⋮ 5 nên x - 2 ∈ B(5) = {0; 5; 10; 15; 20; 25; 30; 35; ...}
x {2; 7; 12; 17; 22; 27; 32; 37; ...}
Mà x ≤ 30
⇒ x ∈ {2; 7; 12; 17; 22; 27}
a)2.x+16=30
2.x=30-16
2.x=14
x=14:2
x=7
vậy x=7
b)\(2.\left(x+1\right)^3+5=59\)
\(2.\left(x+1\right)^3=59-5\)
\(2.\left(x+1\right)^3=54\)
\(\left(x+1\right)^3=54:2\)
\(\left(x+1\right)^3=27\)
\(\left(x+1\right)^3=3^3\)
\(x+1=3\)
\(x=3-1\)
\(x=2\)
vậy x=2
c)x∈U(24) và 2≤x≤12
\(x\in\left\{1;2;3;4;6;8;12;24\right\}\)
mà \(2\le x\le12\)
->\(x\in\left\{2;3;4;6;8;12\right\}\)
vậy \(x\in\left\{2;3;4;6;8;12\right\}\)
d)(x-2):5 và x≤30
x≤30
->\(x=\left\{1;2;3;4;5;6;7;8;...;29;30\right\}\)
->\(x-2=\left\{-1;0;1;2;3;4;5;6....;28\right\}\)
mà x:5
->\(x⋮5\)
->\(x=\left\{5;10;15;20;25\right\}\)
vậy\(x=\left\{5;10;15;20;25\right\}\)